Mild cognitive impairment and progression to dementia of Alzheimer’s disease - Quintes Steiner, Ana Beatriz; Jacinto, Alessandro Ferrari [UNESP]; Mayoral, Vânia Ferreira De Sá [UNESP]; Brucki, Sonia Maria Dozzi; Citero, Vanessa De Albuquerque (FapUNIFESP (SciELO), 2017)
The increase in life expectancy in the Brazilian population raises questions about the preparation of the public health system in identifying elderly patients with signs of cognitive impairment. Currently, as a consequence of the long duration of preclinical phase of Alzheimer’s disease, efforts of early detection have been emphasized. Clinical dementia presents an important impact on the individual’s caregivers, family, society and economy. Identifying individuals who already have some cognitive impairment, despite remaining functional, as well as analyzing associated comorbidities, constitutes an opportunity to analyze possibilities for future interventions. Dementias are clinical conditions that impose a burden on the health system with its high costs, whereas the identification of individuals with cognitive impairment without dementia can aid patients and their families to plan the future and mitigate costs. This narrative revision can provide general practitioners with more information on the subject.
Keywords: Alzheimer’s disease; Cognitive deficits; Diagnosis; Elderly; General practice; Mild cognitive impairment